We're Just Playing: The Influence of a Modified Tabletop Role-Playing Game on ELA Students' In-Class Reading. (April 2017) - Cook, Mike P.; Gremo, Matthew; Morgan, Ryan
Purpose. The purpose of this study was to explored the use of atabletop role-playing game inmiddle school ELA classrooms to examine students' (n=36) abilities to interact with and make meaning from a traditional classroom text (Richard Connell's "The Most Dangerous Game"). Background. Gaming continues to soar in popularity, both inside and outside of schools. As such, it is important to continue looking for pedagogically beneficial ways to incorporate gaming into classroom spaces, specificallyEnglish Language Arts andLiteracy classrooms . Aim. In this article, we describe the game used for this study was modified from the Pathfinder system and designed to pair with Connell's short story. We also discuss our qualitative approach to data analysis, and the three themes that emerged. First, students madegaming decisions based on their knowledge of the story. Second, students experienced the narrative through the lens of their characters. And third, students engaged in meaningful collaboration throughout gameplay. Conclusion. The findings support ongoing calls to look for pedagogically beneficial ways to incorporategaming into ELA and Literacyclassroom spaces.